An Analysis of the Challengers and Barriers of Introducing the Balance Scorecard in Semi Goverment Catholic School in Sri Lanka - Fernando, Mary Selinta; Coonghe, Kingston Darrel; Gunathilaka, L.F.D.Z.; Gunawardana, K.D. (My University, 2016)
Attached

One of the most valuable gifts that the Catholic Church has contributed to the quintessence of Sri Lanka is the education system. The semi government and private schools that we have are headed by the catholic priests, brothers and nuns. Historically and even today the demand for catholic schools is on the incessant increase because of the social, cultural, spiritual and holistic approach to education and life that they contribute to the development of the child. Today, education has become the world‟s second biggest business enterprise. Therefore, there is a great global challenge on the overall performance evaluation of school education is parallel to those of international and government schools. Even though Catholic schools had entered the school education system during the colonial times, the real improvement of the higher education system in Sri Lanka, the significance of the school system in the domain of Sri Lankan higher education is seemingly inadequate. As a cause of concern, this paper is to investigate the benefits, obstacles and challenges in implementing the balanced scorecard (BSC) in catholic schools, more specifically, in Sri Lanka. In today‟s context many schools fail not necessarily because they have the wrong strategy, but due to poor strategy implementation. The balanced scorecard is one of the tools of strategy implementation that integrates the short term operational involvements of a school with the long term strategic direction. It has three additional perspectives over and above the traditional financial perspective. The other perspectives are learning and growth, internal business processes, and customer perspectives, as drivers of future school performance. The findings are particularly relevant to the context of Catholic schools, providing evidence that the BSC can overcome some of the weaknesses of schools inherent in the area of strategic management, as identified by the literature.
Keywords: Balanced Scorecard; Continuous improvement; Customer perspective; Internal business pespective; Learning perspective and Catholic school